489 Sex-based differences in drink-driving across Africa, South Asia, and South America. (20th November 2022) - Suresh, Rachana; Zia, Nukhba; Shah, Janavi; Bachani, Abdulgafoor M
Abstract : Background: Previous studies have demonstrated that male drivers are more likely to indulge in drink-driving compared to female drivers. However, data regarding sex-based differences in drink-driving in LMICs are sparse. Aims: To characterize sex-based differences in drink-driving among motor vehicle users in LMICs. Methods: This study involved secondary analysis of cross-sectional data collected from nine cities- Accra, Addis Ababa, Bangkok, Ho Chi Minh city, Mumbai, Shanghai, São Paulo, Bogota, and Fortaleza, from 2015 to 2019, by Johns Hopkins International Injury Research Unit (IIRU). Descriptive analyses were performed after stratifying drivers based on sex. Discrete variables were assessed as percentages. Comparison between groups was performed using a Chi-squared test. Logistic regression models were used to study the association between drink-driving and sex. Results: Of the total 260, 448 motor vehicles that were observed, the majority of the drivers were male (91.9%). The overall prevalence of drink-driving was found to be 2.4%. It was significantly lower in females (1.2%) versus males (2.5%) (p-value<0.001). Screening tests were requested more commonly from male drivers (80.8%) as compared to female drivers (56.9%) (p-value<0.001). Qualitative screening tests were also performed more frequently on male drivers (76.3%) versus female drivers (52.4%) (p-value<0.001). Adjusting for all other variables, male sex was associated with 1.53 times higher odds of drink-driving as compared to female drivers. Conclusions: Male drivers were more likely than female drivers to be drink-driving in these nine cities. They are also more likely to be screened for drink-driving as compared to their female counterparts.